PEMANFAATAN SUBSTITUSI SLAG WELDING SAW SEBAGAI AGREGAT KASAR PADA BETON - Lilis Tiyani; Sukarman; Andika Sastro Widjoyo (Universitas Widyatama, 2023)
This research, steel welding waste called slag welding SAW was used as a substitute for coarse aggregate in concrete with a content of 50%. This study aims to determine the utilization of SAW welding slag waste as a substitute for coarse aggregate concrete by testing the compressive strength, tensile strength, and flexural strength. The concrete mix design plan uses quality of 25 MPa, using SNI 2834-2000. The specimens for testing the compressive strength of normal concrete and concrete slag welding SAW at the age of 14, 21, and 28 days totaling 18 cubes with a size of 15 x 15 x 15 cm, testing the tensile strength of concrete slag welding SAW at the age of 28 days totaling 2 shapes cylinder with a size of 30 x 15 cm, as well as testing the flexural strength of concrete slag welding SAW at the age of 28 days totaling 2 blocks with a size of 50 x 10 x 10 cm. Slump test of fresh concrete design (60-180) mm. The average compressive strength test results for normal concrete at 28 days were 16,465 MPa. The results of the average compressive strength test of concrete slag welding SAW at 28 days were 15,518 MPa. The average tensile strength test results of slag welding SAW concrete at 28 days were 1.36 MPa. The average flexural strength test results of slag welding SAW concrete at 28 days were 1.17 MPa.